Stevan Stojanović Mokranjac and the inventing of tradition - Tomašević, Katarina (Muzikološki zbornik, 2010)
The main aim of this article is to examine Stevan Stojanović Mokranjac's role in the processes of inventing the artistic tradition of Serbian music of modern times. By following the route of the chosen analytical sample, the folksong 'Cvekje cafnalo' from Mokranjac's Twelfth Garland, through Petar Konjović's works (Symphony C-minor, 1907 and The Second String Quartet, 1937),finally to the piano Sonatina (1926) by Predrag Milošević, I plan to show on which way Mokranjac's oeuvre served as a starting model for the initiation of early modernism in Serbian (and Yugoslav) music in the first half of the 20th century.
Keywords: 1856-1914; 1883-1970; Konjović, Petar; Milošević, Predrag; srbska glasba; Stojanović Mokranjac, Stevan; umetna tradicija